Efektivitas Metode Windows Shopping dalam Meningkatkan Keterampilan Menulis Teks Pidato Siswa Kelas VIII Pada 4 SMP di Cilacap - Wuri Handayani; Ratino Ratino; Heni Kurniawati; Vani Indra Pramudianto; Onok Yayang Pamungkas; Laily Nurlina (Pusat riset dan Inovasi Nasional, 2025)
The effectiveness of the Windows Shopping strategy in enhancing the speech writing abilities of eighth-grade students at four government junior high schools in Cilacap Regency, Indonesia, is examined in this study. The study is based on the demand for novel instructional methods that assist students with the challenges of arranging thoughts, choosing the right vocabulary, and creating well-written sentences while writing speeches. The study used a mixed methods approach with an explanatory sequential design, consisting of pretests and posttests administered to 128 pupils, along with qualitative data from observations, interviews, and reflections. With average scores rising from 61. 63 (pretest) to 81. 97 (posttest), the results showed a notable improvement in students' performance. The statistical significance was confirmed by a paired sample t-test (t = 11. 52, p = 9. 83 × 10⁻¹³). Qualitative data also showed that students were more engaged, creative, and confident during group learning sessions. The Windows Shopping method, in accordance with social constructivist learning principles, encouraged students to actively explore, present, and reconstruct information through group interaction. This approach, according to the study, is effective in improving students' speech writing abilities and promoting essential 21st century skills such as creativity, collaboration, and communication. It should be used more widely in other text-based language instruction as well.